Outcomes before and after Adopting Guidelines for Expectant Management of Severe Preeclampsia - Sanjanwala, Aalok R.; Jauk, Victoria C.; Cozzi, Gabriella D.; Becker, David A.; Harper, Lorie M.; Casey, Brian M.; Tita, Alan T.; Subramaniam, Akila (American Journal of Perinatology, 2020)
Objective This study aimed to compare maternal and neonatal outcomes in women with severe preeclampsia before and after implementation of the American College of Obstetricians and Gynecologists (ACOG) taskforce hypertensive guidelines.Study Design Single-center retrospective cohort study of women with severe preeclampsia delivering live nonanomalous singletons 23 to 342/7 weeks from 2013 to 2017. In 2015, the ACOG guidelines for expectant management of severe preeclampsia were implemented at our institution. Based on this, patients were categorized as preguideline (January 2013–December 2015) or postguideline adoption (January 2016–December 2017). Primary outcomes included composite maternal morbidity and composite neonatal morbidity; secondary outcomes included composite components, length of stay, birth weight, and delivery gestational age. Groups were compared with Student's t-test, Chi-square, and Wilcoxon's rank-sum tests; adjusted odds ratios (aOR; 95% confidence intervals [CIs]) were calculated. Yearly composite outcomes were compared using the Cochran–Armitage trend test. We estimated a sample size of 250 per group would provide 80% power at α = 0.05 to detect a 50% reduction in neonatal morbidity from a baseline rate of 21.5%.Results From 2013 to 2017, a total of 543 women with severe preeclampsia were identified: 278 (51%) preguideline and 265 (49%) postguideline. Baseline characteristics were overall similar between groups. There were no significant differences in maternal (aOR = 0.96, 95% CI: 0.6–1.41) or neonatal (aOR = 0.88, 95% CI: 0.61–1.28) composite morbidity between groups. Furthermore, there were no differences in composite maternal or neonatal morbidity over time.Conclusion Perinatal outcomes were similar before and after implementation of severe preeclampsia management guidelines at our institution. Studies to evaluate if benefits are limited to subsets of this population, such as earlier gestational ages, are needed.Key Points
Keywords: severe preeclampsia; expectant management; maternal morbidity; neonatal outcomes; ACOG guidelines